UPAYA MENINGKATKAN HASIL PUKULAN SWING DALAM PERMAINAN SOFTBALL MENGGUNAKAN METODE RESIPROKAL PADA SISWA KELAS VII SMP NEGERI 3 SEI SUKA TAHUN AJARAN 2013-2014 - Ageng Permadi (Jurnal Pedagogik Olahraga, 2015)
The research purposed to understand the increase in study results a blow swing to their students class viii junior high schools 3 sei like academic year 2013 / 2014 .Research methodology used is research the act of class. To obtain data in this research then done the test results learn prior to the use style teaching resiprokal ( pre-tes ) ago was done learning by using style teaching resiprokal the test results learn i and the test results learn ii who shaped application technique a blow swing as much as 2 meeting. After data collected kinds of analysese: ( 1 ) of a test of study result of the prior to the use the style of teaching resiprokal ( pre-tes ) obtained 5 students ( 20,83 % ) has reached a level ketuntasan learn , while 19 students ( 79,16 % ) have not reached the level ketuntasan learn .And then it would be using the style of learning teaching resiprokal. (3) from the test results learn from cycle i obtained 16 students ( 66,67 % ) has reached a level ketuntasan learning , while 8 students ( 33,33 % ) have not reached the level ketuntasan learning .Then reopened learning .( 3 from the test results learn from cycle ii obtained 21 students ( 87.5 %) reached level ketuntasan learning , while three students ( 12.5 % ) have not reached the level ketuntasan learning In this can be seen that there are repair processes the average score study results cycle i to cycle ii.Based on the results of data analysis be said that through style teaching resiprokal can improve study results technique a blow swing to their students class viii junior high schools 3 sei like academic year 2013 / 2014 Keyword : Improve learning outcomes a blow swing uses the method resiproka